REKONSTRUKSI KONSEP KETATANEGARAAN ISLAM TERHADAP SISTEM PEMERINTAHAN DEMOKRASI PRESIDENSIAL DI INDONESIA - Fauzan Zakir (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
The basic doctrine of Islam is not contrary to democracy and modernization. For example, the doctrine of Islam is advanced enough to support democracy that is parallel to the ideals of modernization. Many Islamic scholars have re-examined the roots and treasures of Islam. Convincingly the Islamic scholars concluded that Islam and democracy were not only compatible; on the contrary, both associations are unavoidable, because the Islamic political system is based on deliberation (syura). A number of Islamic intellectuals and scholars have struggled to find common ground between the Islamic world and the Western world towards a better mutual understanding of the relationship between Islam and democracy. Because, most existing discourse seems too fixated on labels that are used stereotypically by a number of circles. Islam as stated in the hadith: